FAT1 prevents epithelial mesenchymal transition (EMT) via MAPK/ERK signaling pathway in esophageal squamous cell cancer. (1st July 2017) - Hu, Xiaoling; Zhai, Yuanfang; Kong, Pengzhou; Cui, Heyang; Yan, Ting; Yang, Jian; Qian, Yu; Ma, Yanchun; Wang, Fang; Li, Hongyi; Cheng, Caixia; Zhang, Ling; et al.
Abstract: FAT1 regulates cell–cell adhesion, cell growth, cell migration, and actin dynamics as either oncogene or tumor suppressor in human cancers. We previously identified FAT1 was one of significant mutant genes in esophageal squamous cell carcinoma (ESCC). However, the function and underlying mechanism of FAT1 in ESCC have not been explored. In this study, we report that FAT1 expression was significantly lower in ESCC tumor tissues. Exogenous expression of FAT1 led to inhibition of cell proliferation and colony formation, as well as cell migration and invasion whereas FAT1 knockdown showed the opponent trends in vitro and in vivo. Moreover, FAT1 knockdown led to a statistically decrease of E-cadherin expression and a dramatically increase expression of N-cadherin, Vimentin, and Snail in a MAPK/ERK pathway-dependent manner. Meanwhile, over-expression of FAT1 resulted in the opposite trends. These alterations were abrogated in the presence of U0126, a MEK specific inhibitor. Collectively, our studies identified a novel role for FAT1 in inhibiting tumor growth and EMT occurrence in ESCC. We proposed that disruption of MAPK/ERK pathway by FAT1 contributes the EMT in ESCC and has important implications for understanding ESCC development. Highlights: FAT1 is one of SMGs identified in ESCC via next-sequencing analyses. Loss-of-function of FAT1 promotes cell growth and cell migration/invasion in ESCC. FAT1 deregulates EMT in a MAPK pathway-dependent manner in ESCC.